Probing the Line-locking Signatures within the C iv Broad Absorption Line in Quasar SDSS J092345+512710 - Lin, Ying-Ru; Lu, Wei-Jian (The Astrophysical journal, 2020)
Quasar SDSS J092345.19+512710.1 (hereafter J0923+5127) shows two broad absorption line (BAL) systems. The blue one at ∼14,000 km s−1, called BAL system A, has been reported to show a synchronized kinematic shift of its C iv and Si iv BALs. In this paper, we mainly concentrate on the red one at ∼4000 km s−1, called BAL system B, which can be resolved into multiple narrow absorption lines (NALs). We identify 11 NAL systems from BAL system B and find that these blended NALs show complex line-locking phenomena, which offers evidence for the idea that radiation pressure plays an important role in the dynamics of these clumpy outflow clouds.